Subsidence prediction along the karak highway by 2-d electrical imaging geophysical method - Saad, Rosli; Mohd. Noordin, Mohd. Nawawi; Mohamad, Edy Tonnizam (2008)

(untitled)
The KL-Karak highway is one of the expressway connecting Kuala Lumpur (western cost of Malaysia) and Pahang (eastern cost of Malaysia). The area between KM 48.6 to KM 48.8 along the KL-Karak highway is prone to subsidence. Five survey lines using 2D electrical imaging method was run parallel to the highway. The result shows there are few saturated zones (cavity) and fractured zone. Most probably the water flow from line 1 scattered towards line 2, 3, 4 and 5. This could be the reason why frequent subsidence happened along the said stretch. This paper presents the result of the investigations.